THE IMPORTANCE OF PROBLEM SOLVING AND PROJECT WORK IN TEACHING THE ELECTROMAGNETISM DEPARTMENT BASED ON AN INDIVIDUAL LEARNING TRAJECTORY (Web of Technology: Multidimensional Research Journal, 2024)
The article focuses on the importance of problem solving and project work in teaching the department of Electromagnetism based on an individual learning trajectory, and through this, the development of methodological competence by increasing the cognitive potential of students.